Community partnership lessons learned from the You & Me: Test and Treat study - Emily M. D’Agostino; Isa Granados; Princess Abbott-Grimes; Camille Brown-Lowery; Allyn Damman; Tigidankay Fadika; Mark Ward; Mia Cooper; Jeannine Sato; Janet Kasper; Tatiana Vizcaino; Wes Gray; et al. (BMC Public Health)
Abstract Background Community-engaged research relies on the strength of partnerships to achieve and sustain shared goals. The You & Me: Test and Treat (YMTT) project aimed to promote COVID-19 test and treatment access using a tiered model of community engagement and a codeveloped toolkit to foster robust community-academic partnerships. This study assesses the YMTT project’s strengths, identifies partnership lessons learned, and evaluates the toolkit’s utility. Methods This analysis of the YMTT project was conducted from May 2024 to October 2024. A mixed-methods approach was used. Participants represented anchor, local community, and academic partners from YMTT. A validated survey assessed partnership dynamics, including communication, collaboration, and dissemination. The Community Engagement Toolkit Survey and focus groups explored the YMTT partnership strengths and toolkit’s utility, while a collaborative exercise documented reflections on partnership processes. Data were analyzed using descriptive statistics and thematic analysis. Results Twenty-two participants (4 anchor partners, 10 community partners, and 8 academic partners) completed surveys, focus groups, and collaborative exercises. Survey results highlighted strong communication practices (88% agreement on effective, ongoing communication) and mutual respect (88% agreement on valued contributions). Key challenges and themes from the collaborative exercise included trust building, sustainability planning, equitable resource sharing, and accessibility of tools for diverse community partners. Conclusions This study demonstrated that strong communication and mutual respect underpin effective partnerships but highlighted the need for improved sustainability planning and accessible tools. These findings provide a roadmap for enhancing community-academic partnerships and addressing health disparities through equitable, sustainable collaboration. Trial registration ClinicalTrials.gov Identifier: NCT05589376. Registered 21 October 2022.